2016
DOI: 10.1523/jneurosci.3091-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dorsomedial Striatum Neuronal Ensembles in Incubation of Methamphetamine Craving after Voluntary Abstinence

Abstract: We recently developed a rat model of incubation of methamphetamine craving after choice-based voluntary abstinence. Here, we studied the role of dorsolateral striatum (DLS) and dorsomedial striatum (DMS) in this incubation. We trained rats to selfadminister palatable food pellets (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
80
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 73 publications
13
80
3
Order By: Relevance
“…In this regard, we found that inhibition of CeA, AIV, and the AIV→CeA projections decreased active lever presses by ~40–60% but did not completely block drug seeking (i.e., similar active versus inactive lever responding during the relapse test), further supporting the notion that other brain areas and circuits contribute to relapse after voluntary abstinence. Indeed, as mentioned in the Introduction, we recently identified a role of dorsomedial striatum neuronal ensembles in this form of relapse (Caprioli et al, 2017). …”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In this regard, we found that inhibition of CeA, AIV, and the AIV→CeA projections decreased active lever presses by ~40–60% but did not completely block drug seeking (i.e., similar active versus inactive lever responding during the relapse test), further supporting the notion that other brain areas and circuits contribute to relapse after voluntary abstinence. Indeed, as mentioned in the Introduction, we recently identified a role of dorsomedial striatum neuronal ensembles in this form of relapse (Caprioli et al, 2017). …”
Section: Discussionmentioning
confidence: 91%
“…The two levers and the distinct food- and drug-associated cues were located on opposite sides of the self-administration chambers. Next, during the voluntary abstinence period (14 days), we gave the rats a mutually exclusive choice between the palatable food and methamphetamine (20 trials/day, 10 min inter-trial-interval); during the choice trials, the rats can earn either the palatable food or intravenous methamphetamine but not both (a contingency management manipulation) (Caprioli et al, 2015a; Caprioli et al, 2017; Caprioli et al, 2015b; Venniro et al, 2017). On the next day, we tested the rats for relapse to methamphetamine seeking.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, ensembles in the ventral medial prefrontal cortex (mPFC) and orbitofrontal cortex (OFC) were shown to encode the context-induced operant responding for heroin during relapse and after extended abstinence, respectively (Bossert et al, 2011, Fanous et al, 2012). Additionally, ensembles in the dorsal striatum were linked to voluntary abstinence from methamphetamine taking (Caprioli et al, 2017), ensembles in the central amygdala to craving alcohol and nicotine during abstinence (Funk et al, 2016, de Guglielmo et al, 2016), and ventral mPFC ensembles were found to suppress ethanol seeking and drive or inhibit seeking of natural rewards depending on environmental contingencies (Pfarr et al, 2015, Suto et al, 2016, Warren et al, 2016). Importantly, all these studies report a very small number of activated neurons in a given brain region (e.g., <5%), indicating that highly specific addictive behaviors are regulated by small ensembles of neurons throughout the brain.…”
Section: Introduction: Ensembles In Addictionmentioning
confidence: 99%